REVERING NAGA TRIBES AS THE PROPAGATORS OF ECOCENTRISM: RETRIEVING THE EVANESCING CULTURAL HERITAGE THROUGH EASTERINE KIRE’S WHEN THE RIVER SLEEPS - K, Nithya; Albert, Anita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Tribes are always considered as unique people because of their phenomenal culture. The reason is that their culture and its practices are encompassed with fructuous values which assist them in living a prolific life, and frame their lifestyle as an unsophisticated one that facilitates them to live one with nature. In addition, as they primarily reside in mountains, forests, and areas around the water bodies, they follow eco-friendly cultural and traditional customs that instigate them to coexist with their natural environment, and foster the mentality of protecting and preserving their surrounding ecosystem by considering it as their predominant life source. So, they do not possess the attitude of harming or violating their ecological unit; instead, they venerate it. Therefore, they are recognised as ecocentric people. One such ecocentric community is Naga tribes who dwell in the North-Eastern states of India. Even though they are illustrious for their ecocentric way of life, this prestigious identity has been vanishing over time. Further, the entire populace is largely portrayed as uncivilised folk, and they are mostly represented by their faults or misdeeds rather than their goodness or merits. Thus, demonstrating the significance and eminence of their ecocentric and animistic lifestyle, the present research article in d tends to